A New Class of Analytic Normalized Functions Structured by a Fractional Differential Operator - Najla M. Alarifi; Rabha W. Ibrahim (Journal of Function Spaces)
Newly, the field of fractional differential operators has engaged with many other fields in science, technology, and engineering studies. The class of fractional differential and integral operators is considered for a real variable. In this work, we have investigated the most applicable fractional differential operator called the Prabhakar fractional differential operator into a complex domain. We express the operator in observation of a class of normalized analytic functions. We deal with its geometric performance in the open unit disk.